Pemberdayaan Masyarakat Melalui Wisata Danau Ranu di Desa Ranuklindungan Kecamatan Grati Kabupaten Pasuruan - Anandita, Nafisha; Susilo, Heryanto (J+PLUS UNESA, 2024)
Community empowerment, especially in areas that have tourism potential, basically has the aim of realizing community welfare by involving the community's active role in its development. Utilizing natural resources and preserving Lake Ranu tourism can be part of community participation and implementation of empowerment for people who benefit from Lake Ranu tourism. The research method used is a descriptive qualitative method with data collection techniques of in-depth interviews, observation and documentation. The results obtained from this research are the implementation or empowerment process that occurs with daily community activities as traders and community groups who are active in their participation in Lake Ranu tourism, tourism awareness groups who actively carry out major activities which also aim to promote Lake Ranu tourism. Community groups that take advantage of the fish wealth in Lake Ranu and participate in activities held by local community groups and tourism managers. Keywords: Implementation of community empowerment, , Community Groups